Proceedings of the 12th International Conference on Interaction Design and Children 2013
DOI: 10.1145/2485760.2485775
|View full text |Cite
|
Sign up to set email alerts
|

Examining the need for visual feedback during gesture interaction on mobile touchscreen devices for kids

Abstract: Surface gesture interaction styles used on modern mobile touchscreen devices are often dependent on the platform and application. Some applications show a visual trace of gesture input as it is made by the user, whereas others do not. Little work has been done examining the usability of visual feedback for surface gestures, especially for children. In this paper, we present results from an empirical study conducted with children, teens, and adults to explore characteristics of gesture interaction with and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 26 publications
3
28
0
1
Order By: Relevance
“…By placing our discoveries in the larger context set out by previous work on touch-screen interaction design for children [2,3,6,9], we can already anticipate multiple application opportunities made possible by our classification technique: (1) Adaptive widget layouts. Since we know from the literature that children miss onscreen touch targets more often than adults [3], are less precise [9], and have more difficulty with smaller targets [3], children would benefit from an interface layout with larger widgets and more space in-between.…”
Section: Discussion Conclusion and Future Workmentioning
confidence: 99%
See 2 more Smart Citations
“…By placing our discoveries in the larger context set out by previous work on touch-screen interaction design for children [2,3,6,9], we can already anticipate multiple application opportunities made possible by our classification technique: (1) Adaptive widget layouts. Since we know from the literature that children miss onscreen touch targets more often than adults [3], are less precise [9], and have more difficulty with smaller targets [3], children would benefit from an interface layout with larger widgets and more space in-between.…”
Section: Discussion Conclusion and Future Workmentioning
confidence: 99%
“…For instance, we know that gesture recognizers perform worse on children's gestures [3], so the application could benefit from the age group knowledge to know when to activate one recognizer or another [4,10]. Also, we know that visual feedback during gesture input is more important for children than for adults [2], and the app could use the age group data to increase or dim down visual feedback as necessary, which will provide more cues for children and more screen space for adults to display other app widgets and data. (4) Adaptive filtering of content and access to applications.…”
Section: Discussion Conclusion and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, in the preoperational stage children are still developing their cognitive and motor skills and previous research have shown that younger children presented more difficulties to interact with tangible devices than children with a more advanced stage of cognitive development [19], [20], [21]. Numerous children-tablet interactions issues, that can be connected to children continuously development of motor skills, have been previously detected, for instance: difficulties with drag and drop interaction in touch devices [22], [23], [21], difficulties with multi-touch [21], [24], not recognized gestures [20] or misinterpreting touch actions [24], [20]. Other researchers identified aspects related to young children's cognitive development that should be taken into consideration when design tablet application for them, such as holding only one thing at memory at time [25] or manifesting centralization, focusing their attention in only one characteristic at time [21].…”
Section: B Children Cognitive Development and Tablet Interactionmentioning
confidence: 99%
“…Children's gestures have been applied to learn to write letters [20], children peephole navigation using movement-based and touch-base applications have been explored [23], as well the use of stylus pen [21] and the use of the tablet's camera or tangible objects [26]. Although previous works had explored different interaction strategies with children, our literature review indicates that there is still much to be understood regarding children multimodal tablet interactions for serious games, yet more contributions in this field are needed.…”
Section: Multimodal Interaction and Game Instructionsmentioning
confidence: 99%